Ethiopian-affiliated research in Scopus and web of science: A bibliometric mapping - Addisalem Yallew; Asrat Dereb (College of education, Bahir Dar University, 2023)
This paper explores the research landscape in Ethiopia using 20-year data drawn from Scopus and Web of Science (WoS) databases. The focus was to assess yearly research productivity, key research areas, journals in which researchers publish, collaborating countries, languages used to publish papers, and major agencies that fund research. The findings indicate that research productivity has been increasing over the past decades, with biomedical research dominating much of the output. Addis Ababa, Gondar, Jimma, Mekelle, and Bahir Dar universities were identified as the institutions with a relatively higher level of research productivity than the other universities in the country. The top five collaborating countries for Ethiopian researchers were found to be the US, UK, India, Germany, and South Africa. The dominant language of research was English. However, since the country has a strong tradition of producing knowledge in local languages, this finding indicates the need to incorporate research published in African languages in journals and databases.